Normative Virtue Theory in Theological Ethics - Nicholas Austin (Religions, 2017)
What place is there for virtue theory in theological ethics? Many question the normative significance of virtue theory in theological ethics today, leaving it to rule-based ethics to provide action-guidance. There are three key objections to the normativity of virtue theory: that virtue theory is about agents rather than actions, that virtue theory has nothing to say directly about the morality of actions, and that the virtues are too vague to be of normative or action-guiding significance. This essay, drawing on Thomas Aquinas’s account of virtue, challenges these perceptions and argues for a genuinely normative, action-guiding virtue theory within theological ethics. Theological ethics, in turn, can contribute to virtue theory, especially by its emphasis on the ecstatic nature of mature moral virtue, and through its reflection on the virtue of spiritual discernment.